Cybercrime is one of the Sources of Entrepreneurial Risks (Economic journal of Lesya Ukrainka Volyn National University, 2015)
The analysis of offences of willful criminal use of a computer, mobile communication means and methods of their software that are connected to the Internet, mobile communication operators that use the concept of «cybercrime». Distribution of these crimes carried in groups on the content, nature and degree of impact on business results. Shows that by the nature of the impact these crimes directly or indirectly (indirectly) threaten business. The substantiation of the composition of the entrepreneurial risks, which arise as a result of cybercrime. These definitions are formed and place in the system of classification of enterprise risks.